2011
DOI: 10.1021/am200209e
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous Formation of Metal and Metal Oxide Nanoparticles on Carbon Nanotubes and Graphene via Solvent-Free Microwave Heating

Abstract: Microwave irradiation was shown to be an effective energy source for the rapid decomposition of organic metal salts (such as silver acetate) in a solid mixture with various carbon and noncarbon substrates under completely solvent-free conditions. The rapid and local Joule heating of microwave absorbing substrates (i.e., carbon-based) resulted in the instantaneous formation of metal and metal oxide nanoparticles on the substrate surfaces within seconds of microwave exposure. Other less absorbing substrates (suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 85 publications
2
59
0
Order By: Relevance
“…The incorporation of different metal oxide nanostructures on surface of carbon Nano-dimensions substrate let them to be helpful for many applications not just due to particular physical and chemical properties of upheld particles, but furthermore to their big area of the surface, sprightly weight, high mechanical quality, and great electrical and thermal transfer features [5].…”
Section: Ihsciconf2017mentioning
confidence: 99%
“…The incorporation of different metal oxide nanostructures on surface of carbon Nano-dimensions substrate let them to be helpful for many applications not just due to particular physical and chemical properties of upheld particles, but furthermore to their big area of the surface, sprightly weight, high mechanical quality, and great electrical and thermal transfer features [5].…”
Section: Ihsciconf2017mentioning
confidence: 99%
“…The microwave absorbing properties of metallic and aligned multi-walled carbon nanotubes (MWCNTs) have been proposed as a purification procedure during the preparation of semi-conductive CNTs, as well as for a new illumination technology [33]. More recently, the deposition of various metal nanoparticles on MWCNTs has been achieved after the instantaneous decomposition of transition metal acetates under microwaves [34]. It has also been shown that the efficient carbothermal reduction of copper oxide (CuO) can be achieved by microwave heating in the presence of MWCNTs [35].…”
Section: Introductionmentioning
confidence: 99%
“…Some papers also reported that the Ag/graphene or Ag/GO nanocomposites without stabilizing agent in solution were synthesized by kinds of chemical [18e21] or physical [22] methods. Few works were reported with solid-phase reaction to prepare small-sized Ag nanoparticles attached to graphene nanosheets.…”
Section: Introductionmentioning
confidence: 99%